S-nitrosylation-mediated coupling of G-protein alpha-2 with CXCR5 induces Hippo/YAP-dependent diabetes-accelerated atherosclerosis - Meng-Lin Chao (Nature Portfolio, 2021)
S-nitrosylation can influence many pathophysiological processes. Here the authors show that the coupling efficiency of GNAI2 with CXCR5 is enhanced by S-nitrosylation of GNAI2, leading to Hippo-YAP dysfunction in endothelium, and plays a role in diabetes-accelerated atherosclerosis.